Toxicological Effects of Malathion at Low Dose on Wister Male Rats With Respect to Biochemical and Histopathological Alterations - Massoud, Ahmed; SaadAllah, Moustafa; Dahran, Naief A.; Nasr, Nasr Elsayed; El-Fkharany, Ismael; Ahmed, Mohamed S.; Alsharif, Khalaf F.; Elmahallawy, Ehab Kotb; Derbalah, Aly (Frontiers in Environmental Science, 2022)
The toxicity of organophosphorus insecticides is considered a major global health problem, and the target of the toxic action of these compounds in humans and pests is the same. Malathion is the most commonly used organophosphate, and its danger lies in prolonged exposure to low doses. Based on a review of the literature, little is known about the toxicological and clinico-pathological effects of low doses of malathion on animal enzyme activity, such as acetylcholinesterase (AChE), alkaline phosphatase (ALP), glutamic-pyruvic transaminase (GPT), glutamic-oxaloacetic transaminase (GOT) and glutathione S-transferase (GST). Furthermore, the histopathological changes in the organs being studied (liver, kidney, brain, and lung) in treated rats were described. Three groups of experimental animals were created (each with eight rats); two experimental groups and one control group. The first group of rats received a dose of 5 mg/kg malathion orally for 24 h, the second received a dose of 5 mg/kg malathion for 21 days, and the third served as a control. Surprisingly, ALP, GPT, GOT, and GST enzymatic activities increased significantly in both malathion-treated groups (24 h or 21 days), while that of AChE significantly decreased. The histopathological changes were minimal and almost negligible in rats treated with malathion for 24 h. However, multiple histopathological changes were reported in rats treated with malathion for 21 days, including focal hepatocellular necrosis, chronic pyelonephritis, cerebral malaria, interstitial pneumonia, and testicular degeneration. Interestingly, there was a direct correlation between the alterations in biochemical parameters and the histopathological lesions with the prolonged time of low malathion dose administration in rats. The study highlights the importance of research involving malathion’s chronic toxicity by non-lethal low concentrations of malathion to which most people and animals are exposed, whether as residues in water, air, or food.